AN ERROR ANALYSIS ON THE STUDENTS’ RECOUNT TEXT WRITING, A CASE STUDY AT THE FIRST CLASS OF WASKITO SENIOR HIGH SCHOOL - Sunardi, Sunardi (Universitas Pamulang, 2023)
The study aims to conduct error Analysis on the students’ recount text writing, a case study at the first class of Waskito Senior High School. It focuses to get empirical data and to analyze the writing errors made by the students. It is qualitative research with descriptive methods. The subject of the research is the first class students of Waskito Senior High School. While the instrument used is taken from students recount text writing assignment. There are four steps in analyzing the errors, namely identification, description, explanation, and evaluation. The grammatical errors that appear in the students writing are analyzed by using the Surface Strategy Taxonomy proposed by Dulay; (1) omission, (2) addition, (3) miss- selection, (4) miss-ordering. The finding showed that the total of errors is 170 items and they indicated that the most errors were miss- selection (52.3%) and followed by omission (44.1%), addition (2.3%) and miss-ordering (1.1%). Based on the results, it can be concluded that students still have grammatical difficulties in writing recount text. It is hoped it will be beneficial for the parties who involve in educational institution such as English teachers, lectures, students, and other educational practitioners. The writer suggests that the students need to learn more intensively about past tense in recount text, especially the change of verb form both in regular and irregular verbs, as well as the use of auxiliary verbs.